PENGARUH KEBIASAAN BELAJAR TERHADAP HASIL BELAJAR PADA PEMBELAJARAN TEMATIK KELAS V DI MADRASAH IBTIDAIYAH SWASTA AT-TAQWA SAMBAS - Parni Parni; Topik Topik (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
This study discusses the effect of learning habits on learning outcomes in Thematic learning for class V at MIS At-Taqwa Sambas Academic Year 2019/2020. The method used in this research is to use an associative approach and quantitative research types. The results of this study are that there is no influence between study habits on learning outcomes in Thematic learning for class V at MIS At-Taqwa Sambas Academic Year 2019/2020. Based on the results of the correlation calculation, the r number is 0.0243. The simple linear regression equation obtained is Y '= 74.937 + 0.014X. Based on the determinant coefficient calculation of 0.1%. This means that the percentage of the contribution of the influence of the student learning habits variable on the student learning outcomes variable is 0.1%. While the remaining 99.9% is influenced by other factors which are not discussed in this study.